Wiskott-Aldrich Syndrome Presenting with JMML-Like Blood Picture and Normal Sized Platelets - Rajesh B. Patil; Chandrakala Shanmukhaiah; Farah Jijina; Shailesh Bamborde; Nilesh Wasekar; Manoj Toshniwal; Aniket Mohite; Vinod Patil (Case Reports in Hematology)
Objective. The aim of this paper is to report the case of Wiskott-Aldrich syndrome (WAS) that presented with unusual laboratory features. Clinical Presentation and Intervention. Male neonate admitted with symptoms related to thrombocytopenia, whose initial diagnosis was considered as neonatal alloimmune thrombocytopenia and JMML (juvenile myelomonocytic leukemia) but subsequently diagnosis was confirmed as WAS. Conclusion. This case shows that a suspicion of WAS is warranted in the setting of neonatal thrombocytopenia with JMML-like blood picture and normal sized platelets.